“Alcohol is Something That Been With Us Like a Common Cold”: Community Perceptions of American Indian Drinking - Yuan, Nicole P. (2010)
This study examined tribal members’ perspectives on alcohol, risk factors, consequences, and community responses. Focus groups were conducted with five American Indian tribes between 1997 and 2001. Participants were knowledgeable of the cultural lives of their reservation communities. Although there was agreement regarding the pervasiveness of heavy drinking, participants reported different opinions about the meaning of alcohol and appropriate intervention strategies. Three dilemmas were identified, suggesting that community ambivalence may serve as a barrier to reducing problem drinking. Implications, limitations, and future research directions are discussed. The study was funded by the National Institute on Alcohol Abuse and Alcoholism.